Results of Medical Research Council Childhood Leukaemia Trial UKALL VIII (report to the Medical Research Council on behalf of the Working Party on Leukaemia in Childhood). - Eden, O; Lilleyman, J; Richards, S; Shaw, M; Peto, J (1991)
During the 1970s, despite apparently similar treatment, the prognosis for children with lymphoblastic leukaemia (ALL) improved more in some countries, notably the United States and West Germany, than in others. To find out why, the first phase of the United Kingdom (UK) Medical Research Council (MRC) childhood ALL trial, UKALL VIII, was designed to see whether similar results to the United States Children's Cancer Study Group (CCSG) could be obtained in the U.K. using an identical protocol (CCG 162). Protocol 162 was one of a series of regimens devised by the American Children's Cancer Study Group in the 1970s and was used specifically for their average risk patients (all children with ALL with an initial white cell count up to 50 x 10(9)/l except those aged 3-6 years with white cell counts under 10 x 10(9)/l). One arm (1A) of their study was adopted by the MRC for all children in the U.K. aged 0-14 years with confirmed ALL. Eight hundred and twenty-nine consecutive patients were entered between 1980 and 1984. The first 199 patients formed a single arm study as per the original protocol 162 (arm 1A), but the subsequent 630 children were randomized to receive or not two doses of daunorubicin on the first 2 d of induction. This randomization was an attempt to answer the important question as to whether event-free survival was influenced by the use of four rather than three induction agents. A second randomization between 2 and 3 years continuing therapy was also introduced at this stage as it had been by the CCSG in their protocol. With a minimum follow up period of more than 5 years, disease-free survival for the whole group is 55%, a considerable improvement on all previous UKALL trials. Results for patients directly comparable with those in CCSG 162 ('average risk' patients) and their American counterparts were similar. Daunorubicin was associated with more early deaths but improved disease-free survival for those achieving remission. More children relapsed who stopped treatment after 2 years than those who continued for 3, but this was balanced by increased treatment mortality in the third year. The fact that for UKALL VIII the results were similar to those of the CCSG suggests that previous MRC protocols were not sufficiently sustained and intensive, particularly during the maintenance phase of treatment.(ABSTRACT TRUNCATED AT 400 WORDS)